Sketch-based Diagram Editors with User Assistance based on Graph Transformation and Graph Drawing Techniques - Mazanek, Steffen; Rutetzki, Christian; Minas, Mark (Electronic Communications of the EASST, 2011)
In the last years, tools have emerged that recognize sketched diagrams of a particular visual language. That way, the user can draw diagrams with a pen in a natural way and still has available most processing capabilities. But also in the domain of conventional diagram editors, considerable improvements have been achieved. Among other features, powerful user assistance like auto-completion has been developed, which guides the user in the construction of correct diagrams. The combination of these two developments, sketching and guidance, is the main contribution of this paper. It not only shows feasibility and usefulness of the integration of user assistance into sketching editors, but also that novel user strategies for identifying and dealing with recognition errors are made possible that way. The proposed approach heavily exploits graph transformation and drawing techniques. It was integrated into a meta-tool, which has been used to generate an editor for business process models that comprises the features described in this paper.